Intrathecal CAR-NK cells infusion for isolated CNS relapse after allogeneic stem cell transplantation: case report - Jing Yuan; Fuxu Wang; Hanyun Ren (Stem Cell Research & Therapy, 2023)
Abstract A 24-year-old man with central nervous system (CNS) involvement of T-cell lineage acute lymphoblastic leukemia received sibling allogeneic stem cell transplantation (allo-SCT). He developed isolated CNS relapse early post-SCT, while high-dose systemic chemotherapy, intrathecal (IT) triple infusion and IT donor lymphocytes infusion (DLI) all demonstrated effectiveness. We performed IT umbilical cord blood-derived CAR-NK (target CD7) cells infusion, which was not previously reported. After infusion, detection of cytokines revealed that interferon-γ, interleukin-6 and interleukin-8 increased in CSF. He developed high fever, headache, nausea, vomiting and a spinal cord transection with incontinence in a short time, whereas the ptosis and blurred vision improved completely. The bone marrow remained encouragingly complete remission and complete donor chimerism over 9 months after IT CAR-NK cells infusion. In conclusion, IT CAR-NK cells infusion is a potentially feasible and effective option for patients with CNS relapse, with limited neurological toxicity.